PERSEPSI DAN KENDALA GURU DALAM MENERAPKAN E - LEARNING SELAMA PANDEMI COVID -19 DI SMKN 2 BANGLI - Luh Gde Santi Dewi; Made Ayu Purnami (Jurnal Education and Development, 2022)
Covid-19 is an infectious disease caused by a new type of corona virus, namely Sars-coV-2 which was first discovered in Wuhan, China at the end of December 2019. This type of corona virus or better known as Covid-19 is capable of causing mild disturbances in the respiratory system, severe lung infection, even death. The Indonesian government has also taken a policy that aims to reduce the chain of spread of the Covid-19 virus. One of them is by implementing social distancing policies, where residents are required to carry out all activities from home, such as work, study, including worship. The implementation of this social distancing policy clearly has an impact on all sectors of life, including the education sector which is also relatively fatally affected. Learning activities have shifted from face-to-face learning to online learning. The research method used is descriptive qualitative research. The weakness of online learning compared to face-to-face learning is that in online learning the teachers cannot interact with students optimally and students who are less enthusiastic about participating in online learning often do not even take part in learning on the grounds that they do not have an internet quota and also the difficulty of the internet network, so the material presented by the teacher not delivered optimally.